Family with Legius syndrome (neurofibromatosis type 1‐like syndrome). Issue 7 (18th May 2015) - Sakai, Noriyasu; Maeda, Tatsuro; Kawakami, Hiroshi; Uchiyama, Masaki; Harada, Kazutoshi; Tsuboi, Ryoji; Mitsuhashi, Yoshihiko
Abstract Legius syndrome (Online Mendelian Inheritance in Man no. 611431) or neurofibromatosis type 1 (NF1)‐like syndrome was first reported by Legius et al. in 2007. We herein report the first instance of Legius syndrome occurring in two female siblings in Japan. Both individuals presented cafe‐au‐lait macules and freckling. Mutation analysis revealed a mutation of c.349C>T resulting in p.Arg117* in the SPRED1 gene as the cause of the Legius syndrome. The National Institutes of Health criteria for NF1 are insufficient to rule out the condition. For this reason, and because the clinical course of each condition is quite different, we stress the need to differentiate Legius syndrome from NF1 clearly.